Labour migration and social networks participation in southern Mozambique (2013)
This paper investigates how social networks in poor developing settings are affected by migration. Using a unique household survey from southern Mozambique, we test the role of labour mobility in shaping participation in groups and interhousehold cooperation by migrant-sending households in village economies at origin. We find that migration cum remittances boosts household engagement in community-based social networks. Our findings are robust to alternative definitions of social interaction and to endogeneity concerns, suggesting that stable migration ties and higher income stability through remittances may decrease participation constraints and increase household commitment in cooperative arrangements in migrant-sending communities. © 2013 The London School of Economics and Political Science.